Computational simulation of Casson hybrid nanofluid flow with Rosseland approximation and uneven heat source/sink - G. Ramasekhar; F. Mebarek-Oudina; S. Suneetha; H. Vaidya; P.D. Selvi (International Journal of Thermofluids)
This article candidly presents the magnetohydrodynamics Casson hybrid nanofluid flow over a stretching surface. In the present study, we added a nonuniform heat source or sink and non-linear thermal radiation. We considered Al2O3 and copper nanoparticles to have antibacterial and antiviral properties without any harmful impacts and used water as the host fluid. We simplified the governing flow equations by using suitable self-similarity variables, which are used to convert PDEs to ODEs. The mathematical equations are numerically solved by using the bvp5c technique in the MATLAB software. Additionally, with higher values of the magnetic field and Casson fluid parameters the velocity profile decreased. The temperature profile is enhanced by increasing the magnetic field and thermal radiation parameters. Increasing the Casson fluid and radiation parameters enhances the skin friction and Nusselt number profiles. Alumina nanoparticles find applications in cosmetic fillers, polishing materials, catalyst carriers, analytical reagents. Copper nanoparticles have high electrical conductivity, which has many uses in electrical circuits and biosensors.